Should religion be permitted a seat at the table of bioethics? The case of abortion - Giubilini, A (Springer, 2024)
In addressing the question whether religion should be permitted a seat at the table of bioethics, and specifically where abortion is discussed, I argue that the question requires first some disambiguation. There is a sense in which the answer is obviously affirmative, but also a sense in which the answer is problematic. In particular, when it comes to bioethical discussion about the appropriate scope of the healthcare profession and about policy making, I argue that religion itself is neither sufficient nor necessary for deliberating about abortion in liberal societies. However, even if its role is neither sufficient nor necessary, religion can still have an important role to play in that kind of deliberation. Its values and norms can be grounded in non-religious views, such as natural law theory, that are relevant indeed to bioethical discussion on abortion. Thus, religion – and particularly Christianity - can be one route into that kind of bioethical discussion for many people. However, while these values and norms might well be valid and widely supported, they are also open to public scrutiny, political negotiation, and, in some cases, defeat. Those supporting the role of religion in bioethical discussion on abortion would need to accept this implication.